Impact of Metabolic Syndrome Factors on Testosterone and SHBG in Type 2 Diabetes Mellitus and Metabolic Syndrome - Mukhtar Mohammed; Molham AL-Habori; Ahmed Abdullateef; Riyadh Saif-Ali (Journal of Diabetes Research)
Objective. Several studies have often reported low testosterone and SHBG to be associated with type 2 DM and the metabolic syndrome (MetS). Our objective was to determine the impact of metabolic syndrome and diabetic parameters on testosterone and SHBG in both MetS subjects and type 2 DM patients. Methods. In this study, 120 Yemeni male aged 30–70 years old were enrolled, 30 of whom were healthy subjects with BMI < 25 kg/m2 that served as control, 30 MetS, 30 type 2 DM without MetS, and 30 type 2 DM with MetS according to IDF criteria. Results. Testosterone (free and total) and SHBG were significantly lower in MetS subjects and modestly reduced in type 2 DM with and without MetS. Stepwise linear regression showed free and total testosterone to be negatively affected by waist circumference, and univariate analysis shows this significant difference to disappear when adjusted for waist circumference. On the other hand, stepwise linear regression showed SHBG to be positively affected by testosterone and age and negatively affected by FBG and TG. Univariate analysis shows this observed significant difference to disappear when adjusted for testosterone. Conclusion. Abdominal obesity is a major determinant of low testosterone levels irrespective of diabetes status. Thus, supporting evidence suggesting that the causative relationship between the often low testosterone and type 2 DM might be bidirectional or even multidirectional and interrelated with obesity, MetS, and IR.